Case report: A case of oviductal and uterine leiomyosarcoma in an 11-year-old dog - Kazmierczak, Jillian; Sugai, Nicole J.; Withowski, Katie E.; Jonatan, Abe; LeRoith, Tanya; Cecere, Julie T. (Frontiers in Veterinary Science, 2023)
An 11-year-old, intact female Pomeranian dog was presented for evaluation due to an 18-hour history of anorexia and lethargy. Abdominal ultrasound revealed a 3x3 cm mass of mixed echogenicity at the level of the left ovary. At laparotomy, a 5 mm mass was identified at the cranial region of the right uterine horn and a 3 cm round mass was visualized near the cranial aspect of the left uterine horn. Ovariohysterectomy was performed. A diagnosis of grade 1 oviductal and uterine leiomyosarcoma was made via histopathology for both masses. Oviductal leiomyosarcomas are rare and generally locally invasive similar to other soft tissue sarcomas but do not often metastasize. Uterine leiomyosarcomas are also uncommon but are one of the more common tumors affecting the female reproductive tract. This is the only known case report of oviductal leiomyosarcoma in the dog and the only report of uterine leiomyosarcoma in addition to oviductal leiomyosarcoma as well. This case illustrates the oviduct as an additional site that can be affected by leiomyosarcoma and demonstrates surgery as a treatment option for patients diagnosed with this condition. Background Female reproductive tract neoplasms are an uncommon finding in small animal veterinary medicine. Ovarian tumors only have a prevalence of 0.5-1.2% in the dog (1). Uterine tumors are even more uncommon making up only 0.3-0.4% of all canine and feline tumors (1, 2, 3). Some of this rarity is likely attributed to the fact that many female companion animals are ovariohysterectomized at a young age. The most commonly reported reproductive tract neoplasms include ovarian carcinomas, granulosa-theca cell tumors (GTCT), and uterine tumors including benign leiomyomas and fibromas. More uncommon are malignant neoplasms such as leiomyosarcomas, fibrosarcomas, and adenocarcinomas (1). There is no reported data on the